Structural and transport phenomena of urocanate-based proton carrier in sulfonated poly(ether ether ketone) membrane composite - Nimmanpipug, Piyarat; Kodchakorn, Kanchanok; Lee, Vannajan Sanghiran; Yana, Janchai; Jarumaneeroj, Chatchai; Phongtamrug, Suttinun; Chirachanchai, Suwabun (Wiley, 2018)
Proton transport is one of crucial phenomena in electrolytic part highly considered to overcome a limit in fuel cell efficiency improvement. Proton conducting organic electrolyte was modeled and simulated at atomistic level of calculation by doping of butyl urocanate (C4U), a composite material with imidazole substructure, with sulfonated poly(ether ether ketone) (SPEEK) amorphous membrane at various working temperature. Molecular dynamics simulations were used to investigate structural and dynamics characteristic of C4U in the membrane comparing with the SPEEK-hydronium membrane model as a control. From simulations, thermal effect on water and proton carriers cluster surrounding the sulfonate groups was explored. At higher temperature, the more transport dynamics of C4U ions in SPEEK membranes were found than that of hydronium ions in the control system. Likewise, phase separation of hydrophobic and hydrophilic parts was taken into consideration here. A critical role of the enhancing proton conductivity by increasing the diffusion coefficient at temperature beyond C4U melting point in composite polymer membrane was emphasized.